Doris Lessing: Ã¢â‚¬Å“The free womanÃ¢â‚¬â„¢s commitmentÃ¢â‚¬Â - Gautam, Mahima (International Multidisciplinary Research Journal, 2011)
The paper aims at describing the free woman’s commitment in the novels of Doris Lessing. The personal agonies, traumas, the dissolution of marriage of her women characters aims to depict man-woman relationship, which is one of the major themes in her works. Marriage is the deepest as well as the most problematic of all human relations. Doris Lessing delineates with keen perception and sensitivity, the problems and sufferings of women in marriage. Women feel entrapped, oppressed and doomed to the care of husband and home, the reaction which she shows in her novels. Some of her women characters accept their fate unhestitatingly, but most wants freedom and gradually go for separation or for divorce to live a meaningful life. After studying her novels I find that the tradition of family is very strong, and thus makes a strong plea for the preservation of it by inviting men to involve themselves in it.